Shifting Trends in Business English Assessments: A Comparative Study of Pre- and Post-Pandemic Outcomes - Katarzyna, Fronczak; Makowska, Aleksandra Beata (2024)
This study compares online and onsite final exams for the Business English Course at the University of Lodz during and post-pandemic. It aims to evaluate how testing environments influence exam outcomes. Hypothesising that online testing yields superior results, the study compares exams conducted in the summers of 2020/2021 (online) and 2021/2022 (onsite) for students who completed a three-term online Business English course. Quantitative methods were employed to analyse correlations between testing conditions, supplemented by student surveys. The findings not only shed light on student attitudes but also offer insights crucial for refining future assessment practices in Business English courses and beyond. The research underscores the imperative of meticulously crafted online tests and equitable testing conditions to ensure the integrity and validity of educational evaluations amidst the dynamic landscape of remote learning.
Keywords: Business English; COVID-19; distance learning; final assessment; online testing; onsite testing